Association Between Bacterial Vaginosis and Squamous Intraepithelial Lesions of the Uterine Cervix - Dabeski, Drage; Danilovski, Dragan; Antovska, Vesna; Basheska, Neli; Stojovski, Marjan; Popovska, Zora; Buklioska, Adriana; Avramovska, Maja (Македонско лекарско друштво = Macedonian medical association, 2016)
Introduction. Bacterial vaginosis is polymicrobial, primarily anaerobic infection, previously called non-specific vaginitis or vaginitis accompanied by Gardne-rella vaginallis. It is a result of an imbalance between different types of bacteria in the vagina. The aim of the study was to determine the association between bacterial vaginosis and squamous intraepithelial lesions of the uterine cervix. Methods. This cross-sectional study was conducted in a series of 338 sexually active women with cytologicallly diagnosed squamous intraepithelial lesion of the uterine cervix at the University Clinic of Gynecology and Obstetrics in Skopje in the period from October 2014 to October 2015. The age of the patients ranged from 20 to 59 years (35±10.49). All women underwent cervical biopsy with endocervical curettage for histopathological analysis and cervical biopsy for detection and HPV typing. Criteria for diagnosis of bacterial vaginosis was the presence of ≥20% clue cells of ePapanicolaou smear. Results. Bacterial vaginosis was detected in 19.5% (66/338) of the examined women. The most affected was the young population under the age of 30 years. The results showed an association between bacterial vaginosis and squamous intraepithelial lesions of the uterine cervix (p=0.032). There was no association between bacterial vaginosis and the grade of lesion of the uterine cervix (p=0.118), nor with HPV infection (p=0.570). But, however an association was found between HPV infection and squamous intraepithelial lesions of the uterine cervix (p=0.001). Conclusion.The most common risk factor for squamous intraepithelial lesions of the uterine cervix are persistent high-risk HPV infections. Bacterial vaginosis is the most common co-infection.
АСОЦИЈАЦИЈА ПОМЕЃУ БАКТЕРИСКАТА ВАГИНОЗА И СКВАМОЗНИТЕ ИНТРАЕПИТЕЛНИ ЛЕЗИИ НА ГРЛОТО НА МАТКАТА
Keywords: bacterial vaginosis; intraepithelial lesions; clue cells; human papillomavirus